Use bioremediation technique to remove some heavy metal ( Zn , Ni , Co , Mn) Laboratory - Ammar Ahmed, Qassim; Al-Kalidy, Saad Kadhim Ala Allah; Aliwy Hassan, Hussein (Al-Qadisiyah Journal of Pure Science, 2018)
The current study was conducted to investigate the effect of different concentration of heavy metal on physiological state for same aquatic plant by study accumulation of heavy metal within tissues and determine concentration of total chlorophyll and protein through exposure of two aquatic plants Myriophyllum verticillatum , Ceratophyllum demersum for three concentration of heavy metal (10,20,30) ppm as Zink chloride Cobalt chloride Manganese chloride Nickel chloride for 5 weeks ,The results of study demonstrated height various in concentration of heavy metal in tissue of the plant in the end of experiment and the aquatic plant response the through determine of concentration of total chlorophyll and protein were studied the result show decrease concentration of total chlorophyll and protein for the aquatic plant .